2014
DOI: 10.1016/j.appet.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

12Month changes in dietary intake of adolescent girls attending schools in low-income communities following the NEAT Girls cluster randomized controlled trial

Abstract: Poor dietary habits and obesity are more prevalent in lower socio-economic status (SES) communities. The NEAT Girls cluster randomized controlled trial was a school-based obesity prevention program targeting adolescent girls in low SES schools in NSW, Australia. The aim was to evaluate the 12-month impact of key nutrition program messages on dietary intake and food behaviors. Diet was assessed using a validated semi-quantitative food frequency questionnaire (FFQ). Individual foods were categorized into nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(121 citation statements)
references
References 44 publications
1
116
1
3
Order By: Relevance
“…Having an estimate of the servings of the food groups, each group was multiplied by the equivalent amount of calories from the eight groups (Philippi, 2014), and, finally, the groups were added and the total energy intake was calculated. Energy intake Ͻ 500 kcal and Ͼ 5.000 kcal were removed from database (57 from baseline and 29 post-intervention) (Collins et al, 2014;Leal et al, 2010). The eight food pyramid groups were divided into four levels according to their main nutrient composition:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having an estimate of the servings of the food groups, each group was multiplied by the equivalent amount of calories from the eight groups (Philippi, 2014), and, finally, the groups were added and the total energy intake was calculated. Energy intake Ͻ 500 kcal and Ͼ 5.000 kcal were removed from database (57 from baseline and 29 post-intervention) (Collins et al, 2014;Leal et al, 2010). The eight food pyramid groups were divided into four levels according to their main nutrient composition:…”
Section: Discussionmentioning
confidence: 99%
“…Outside of the home, school-based settings are the only institutions that have a continuous and intensive connection with children and adolescents during the first two decades of life and are a socialization agent that can favorably influence the health of children (Robinson et al, 2014). Although school-based obesity prevention programs with Brazilian adolescents are limited (Guerra et al, 2014), methodologically rigorous trials have demonstrated that these interventions can improve diet in youth (Collins et al, 2014;Neumark-Sztainer et al, 2010;Smith et al, 2014b;Singh et al, 2009). Therefore, the aim of this study was to evaluate the effects of a school-based obesity prevention program targeting Brazilian adolescent girls on dietary intake and meal frequency.…”
mentioning
confidence: 99%
“…The NEAT Girl studies have targeted inactive adolescent girls from low-income backgrounds ("at risk" for obesity). Although NEAT Girls did not alter the primary outcome (BMI), it presented small changes in other health behaviors such as PA, screen time, and dietary intake 11,40 . Likewise, the New Moves intervention program targeted adolescent girls who were overweight or "at risk" for obesity 23 .…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the number of servings from the food groups were calculated and used as the dependent variables in the analyses. Energy intake ≤500 kcal and ≥5000 kcal were removed from database (57 from baseline) [25].…”
Section: Dietary Intakementioning
confidence: 99%